Upright Radiation Therapy—A Historical Reflection and Opportunities for Future Applications - Rahim, Sulman; Korte, James; Hardcastle, Nicholas; Hegarty, Sarah; Kron, Tomas; Everitt, Sarah (Frontiers in Oncology, 2020)
Since the early days of megavoltage Radiation Therapy (RT), the potential of delivering treatment to a sub group of patients in an upright position has been recognised. Compared to lying horizontally, treating patients in an upright position offers potential benefits in terms of patient comfort especially for patients experiencing dyspnoea and saliva accumulation when lying down. Dosimetric benefits can also be gained from changes in the volume and location of lungs and heart in an upright position, which are potentially advantageous for clinical situations including Hodgkin’s disease, lung and breast malignancies. Since the 1950’s, upright stabilisation mechanisms have ranged from standalone chair based apparatus to couch-top attachments with increasingly customisable solutions. The introduction of Computed-Tomography (CT) based three-dimensional (3D) dosimetry in the 1980’s – 90’s necessitated image acquisition in a horizontal position (supine or prone), significantly reducing options for alternative patient positioning and upright techniques. Despite this, upright techniques have still been utilised where clinically indicated for palliative and novel approaches often involving non-standard treatment scenarios. More recently, a small number of centres have reported on specialised equipment capable of acquiring planning data with the patient in a vertical position. The possibility of acquiring planning quality Cone Beam CT (CBCT) on linear accelerators has recently reinvigorated the potential to deliver highly accurate and targeted treatments to patients in an upright position. This paper reflects on the historical applications of upright RT and explores new possibilities for this technology in modern RT departments.